Transforming growth factor beta 3 induced human adipose-derived stem cells for auricular chondrogenesis - Siti Nurhadis Che Omar,; Goh, Bee See; Muhammad Azhan Ubaidah,; Khairul Anuar Khairoji,; Shamsul Sulaiman,; Lokman Saim,; Chua, Kien-Hui (Penerbit Universiti Kebangsaan Malaysia, 2018)
The limitation of self-repair and proliferation capacity of chondrocytes in cartilage reconstruction lead to alternative search of cell source that can improve the auricular regeneration. Human adipose-derived stem cells (HADSC) are an alternative cell source that have unique characteristics to self-renew and differentiate into various tissues making it suitable for cell therapy and tissue engineering. This study aimed to examine the chondrogenic differentiation potential of (HADSC) in monolayer culture by the presence of different transforming growth factor beta’s, TFG-β1, -β2 and -β3. HADSC at passage 3 (1.5 × 105 cell/mL) were cultured in chondrogenic medium containing 5 ng/mL of different transforming growth factor beta’s, TFG-β1, -β2 and -β3 for 7, 14 and 21 days. Data analysis was evaluated based on the growth rate of cells, cells morphological changed, production of collagen type II and glycosaminoglycan sulphate (sGAG). The quantitative RT-PCR was carried out to determine the chondrogenic, fibrogenic and hypertrophic gene expression levels. Differentiation of HADSC into chondrocytes using TFG-β indicates the occurrence of the chondrogenesis process. The best chondrogenic differentiation was observed in HADSC induced by TFG-β3 through the chondrocytes-like cells morphology with cells aggregation and high production of proteoglycan matrices compared to other TGF-βs groups. Additionally, the expression of chondrocytes-specific genes such as Type II collagen, Aggrecan core protein, Elastin and Sox 9 was high. In conclusion, this study has showed that TGF-β3 is the potential growth factor in producing chondrogenic cells for auricular cartilage tissue engineering.